The Theory and Practice of Academic Entrepreneurialism: Transborder Polish-German Institutions - Kwiek, Marek (My University, 2013)
In this paper I discuss academic entrepreneurialism in the empirical context of Polish-German transborder universities. Entrepreneurialism is viewed here, following Michael Shattock (2009a: 3), as “a drive to identify and sustain a distinctive institutional agenda which is institutionally determined, not one [which is] effectively a product of a state funding formula”. Entrepreneurial universities seem to be increasingly important points of reference for international and European-level policy discussions about the future of higher education. The major question of this paper is as follows: how do Polish-German transborder universities respond to the challenges of changing social and economic environments and to what extent they are able to determine their futures?
Keywords: academic entrepreneurship; academic entrepreneurialism; Burton R. Clark; non-core income; Viadrina University; Polish universities; enterprise universities; public-private; foundation universities; German university; university governance; higher education policy; public policy; Polish-German cooperation; transborder universities; transborder cooperation; university cooperation